Avoiding Middle-income Trap in Muslim Majority Countries: The Effect of Total Factor Productivity, Human Capital, and Age Dependency Ratio - Seyed Hossein Mirjalili; Amin Mohseni Cheraghlou; Hossein Sa'adat (International Journal of Business and Development Studies, 2018)
In 2010, the World Bank categorized countries in per capita gross domestic product in terms of purchasing power parity (at constant 1990 prices) in three categories: low, middle (lower and upper) and high income. If a country caught at least 28 years in lower middle income level and at least 14 years caught in upper middle-income level, then they are trapped in lower middle and upper middle income traps respectively. The growth of per capita GDP or economic growth, is a factor in avoiding middle income trap. We examined the effect of total factor productivity, human capital and age dependency ratios on GDP per capita growth and the avoidance of middle income trap during 1991 - 2014 for ten Islamic countries, using panel data and constant effects estimation. The findings indicate that human capital and then total factor productivity have positive and significant relationship with percapita GDP and have the greatest impact on economic growth and the avoidance from middle income trap. If the ratio of age dependency is high, it has a positive and significant effect on economic growth and can keep the country in the middle income trap.
Keywords: 330; middle income trap; Islamic countries; total factor productivity; age dependency ratio; human capital